Leaky wave in high-power AlGaAs/InGaAs/GaAs semiconductor lasers. (August 2020) - Bobretsova, Yu.K.; Veselov, D.A.; Klimov, A.A.; Kryuchkov, V.A.; Shashkin, I.S.; Slipchenko, S.O.; Pikhtin, N.A.
Abstract: Lasers based on AlGaAs/InGaAs/GaAs heterostructures operating in the spectral range of 1.0 − 1.1 μm are investigated in order to optimise cladding layers. The effect of the thickness and composition of the cladding layers on the leakage of radiation from the laser waveguide is analysed. It is shown that for cladding thicknesses of 0.86 − 1.24 μm, it almost does not affect the output optical power. The effect of the crystal length and reflectivity of the laser mirrors on the leaky wave is demonstrated.